Kajian Faktor Yang Memengaruhi Adopsi Sistem Pijaman Peer To Peer Lending - Soegesty, Nugraha Bagoes; Fahmi, Idqan; Novianti, Tanti (SBM ITB, 2020)
Abstract. Medium, Small, Micro Entrprices (MSME) have a big role to play in the economy in Indonesia. Kemenkop UMKM (2017) states that as many as 80.9% of micro businesses in Indonesia do not yet have access to bank financing. One way to overcome barriers to MSME lending is through financial technology interventions through peer-to-peer lending (P2P lending) financing. The purpose of this study is to analyze the factors influencing MSME intention and behavior to use P2P lending services using the UTAUT2 analysis model (Venkantesh et al. 2012) with Structural Equational Modeling (SEM) analysis tools. The results of this study indicate that there are four variables that strongly and positively influence the intention to use P2P lending services among MSMEs, namely hedonic motivation, social influence, effort expectation, and performance expectancy. Then the results of this study also show that the behavior of using P2P lending services is strongly and positively influenced by gorenment regulation, risk perception, and behavioral intention.Keywords: MSME, P2P lending, Structural Equation Modeling (SEM), and UTAUT2Abstrak. UMKM memiliki peran yang besar terhadap perekonomian di Negara Indonesia. Kemenkop UMKM (2017) menyatakan bahwa sebanyak 80.9% usaha mikro di Indonesia belum mendapatkan akses pembiayaan perbankan. Salah satu cara untuk menyelesaikan hambatan penyaluran kredit UMKM adalah melalui intervensi teknologi finansial melalui pembiayaan `peer-to-peer lending (P2P lending). Tujuan dari penelitian ini adalah menganalisis faktor-faktor mempengaruhi niat dan perilaku UMKM untuk menggunakan layanan P2P lending dengan menggunakan model analisis UTAUT2 (Venkantesh et al. 2012) dengan alat analisis Structural Equational Modeling (SEM). Hasil dari penelitian ini menunjukkan bahwa terdapat empat variabel yang secara signifikan memengaruhi niat penggunaan layanan P2P lending dikalangan UMKM yaitu hedonic motivation, social influence, effort expectacy, dan performance expectancy. Kemudian hasil penelitian ini juga menunjukkan bahwa perilaku penggunaan layanan P2P lending dipengaruhi secara signifikan oleh gorenment regulation, risk perception, dan behavioral intention..Kata kunci: P2P lending, Structural Equational Modeling (SEM), UMKM, dan UTAUT2